2022
DOI: 10.3389/fenvs.2022.1067534
|View full text |Cite
|
Sign up to set email alerts
|

Tax incentives and green innovation—The mediating role of financing constraints and the moderating role of subsidies

Abstract: Government intervention is increasingly vital due to the dual externalities of green innovation. We explored the relationship between tax incentives, subsidies, and green innovation. Based on data from Chinese listed companies from 2010 to 2019, we developed an evaluation system for corporate green innovation. First, we find that tax incentives promote corporate green innovation, while subsidies have little effect on green innovation. Second, we find that financing constraints are the main path of influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Furthermore, tax burden may reversely moderate the relationship between CEO's green ecological experience and green innovation. The reason is that tax burden causes financial restraints for enterprises as the revenue may be received in the long-term and cannot be directly return (Voegtlin and Scherer, 2017;Wang et al, 2023a). Due to the high complexity of green innovation, enterprises may take the green innovation decision into account seriously (Wang and Yu, 2021).…”
Section: Sys-gmm Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, tax burden may reversely moderate the relationship between CEO's green ecological experience and green innovation. The reason is that tax burden causes financial restraints for enterprises as the revenue may be received in the long-term and cannot be directly return (Voegtlin and Scherer, 2017;Wang et al, 2023a). Due to the high complexity of green innovation, enterprises may take the green innovation decision into account seriously (Wang and Yu, 2021).…”
Section: Sys-gmm Methodsmentioning
confidence: 99%
“…By paying taxes on time, they have more standardized management mechanisms for using funds. The tax incentive and financing funds to "A-level" enterprises reduce the financial constraints and are conducive to the enterprise to invest sufficient capital into green innovation to achieve sustainable development (Guo, 2022;Wang et al, 2023a). Frontiers in Environmental Science frontiersin.org 5.3.2.2 The moderating effect of tax burden on the CEO's green ecological experience and corporate green innovation Regression results are shown in Table 6.…”
Section: The Moderating Effect Of Tax Credit Rating On the Ceo's Gree...mentioning
confidence: 99%
See 1 more Smart Citation
“…Wolde-Rufael and Mulat-Weldemeskel (2021) assessed the effectiveness of environmental taxes and environmental policy instruments in reducing CO2 emissions in seven emerging economies over the period 1994-2015, and found that strict environmental policies and environmental taxes were effective in reducing CO2 emissions. Based on data from Chinese listed companies from 2010 to 2019, Wang C et al (2022) developed an evaluation system for corporate green innovation and found that tax incentives promoted corporate green innovation. However, a few studies have concluded that environmental control policies such as environmental taxes are not effective on the environment.…”
Section: Environmental Impact Of Export Tax Rebatesmentioning
confidence: 99%
“…As the “ballast stone” of China’s economy, the extensive development mode of the manufacturing industry has brought great pressure on the ecological environment. Therefore, the green development of the manufacturing industry has become the strategic focus of China’s continuous promotion [ 3 , 4 ]. As emphasized in the “14th Five-Year Plan for Industrial Green Development”, the next five years will be a critical period for implementing the strategy of manufacturing power and a crucial stage for the realization of green manufacturing.…”
Section: Introductionmentioning
confidence: 99%